Self-medication and use of medicinal plants among university students in the Peruvian Amazon during the first wave by COVID-19 - Pasache Pinedo, Piero (2023)
Introduction: The accelerated spread of SARS-CoV-2 brought about a worldwide crisis, and a series of studies and recommendations to manage it. Before the pandemic, studies evidence a high prevalence of self-medication in university students. Objective: To identify the frequency and characteristics of self-medication against COVID-19 with drugs and/or medicinal plants in students of the National University of the Peruvian Amazon (UNAP), Iquitos, Loreto-Peru, during the first wave of COVID-19. Material and Methods: A descriptive cross-sectional study was conducted on 338 students using a semi-structured ad-hoc survey with questions distributed in 3 dimensions: sociodemographic characteristics, characteristics of COVID-19, and characteristics of the use of drugs/medicinal plants. Results: The mean age was 22.39 years (SD ± 5.59), female sex predominated with 61.2 % (n=207), and 55.3 % (n=187) presented symptoms suggestive of COVID-19. In addition, 76.9% (n=260) used medication, distributed from highest to lowest 65.4% (n=170) drugs and plants, 25.8% (n=67) only plants, and 8.8% (n=23) only drugs; 79.2% (n=206) used self-medication. The main drugs used were dexamethasone, paracetamol, azithromycin, and ivermectin. The main medicinal plants used were eucalyptus, kion, chamomile, and matico. There was a probable association between self-medication and a history of symptoms suggestive of COVID-19 (p=0.001, 95% CI), and COVID-19 contact (p=0.011, 95% CI). Conclusion: Among students of a university in the Peruvian Amazon, a high prevalence and factors associated with self-medication with drugs and medicinal plants were identified.